Association of cardiometabolic markers with hepatic steatosis and liver fibrosis in population without obesity and diabetes - Zhixing Fan; Chaojun Yang; Xiaojing Zhao; Jing Zhang (Scientific Reports)
Abstract The link between cardiometabolic markers and hepatic steatosis and liver fibrosis in non-hypertensive, non-diabetic populations remains unclear. A study was conducted using data from the National Health and Nutrition Examination Survey. Hepatic steatosis and liver fibrosis were assessed using vibration-controlled transient elastography. Logistic regression and restricted cubic splines (RCS) were used to evaluate the associations of cardiometabolic index (CMI), atherogenic index of plasma (AIP), triglyceride-glucose index (TyG), and estimated glucose disposal rate (eGDR) on hepatic steatosis and estimated fibrosis. Mediation analysis examined the role of insulin resistance (HOMA-IR) and liver enzymes. Among 1489 participants, 39.15% had hepatic steatosis and 2.82% had liver fibrosis. Higher CMI (OR = 3.967, 95%CI: 2.297, 6.851), AIP (OR = 3.255, 95%CI: 2.031, 5.216), TyG (OR = 3.689, 95%CI: 2.363, 5.760), and FLI (OR = 2.695, 95%CI: 1.997, 7.816) tertiles of Q3 were linked to increased hepatic steatosis odds, while eGDR reduced odds (OR = 0.217, 95%CI: 0.127, 0.373). The AUC values of these four cardiac markers were greater than FLI, among which eGDR showed the highest predictive value (AUC = 0.781). In the hepatic steatosis population, CMI (OR = 1.419, 95%CI: 1.033, 2.747), AIP (OR = 5.527, 95%CI: 1.082, 28.242), and TyG (OR = 2.345, 95%CI: 1.180, 4.661) were also showed significant association with liver fibrosis, while eGDR and FIB-4 were not associated with liver fibrosis. AIP had the highest discriminative ability for liver fibrosis (AUC = 0.798). Mediation analysis showed HOMA-IR mediated 25.50%~36.20% of cardiometabolic markers’ associations with hepatic steatosis, followed by liver enzymes. Cardiometabolic markers are strongly linked to hepatic steatosis and liver fibrosis in populations without traditional risk factors, even outperforming the established hepatic steatosis and the fibrosis marker, highlighting their potential for early liver disease risk identification in seemingly healthy individuals.